2012
DOI: 10.1002/etc.1903
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biodegradation and sorption of phthalate esters and their metabolites in natural sediments

Abstract: Regulatory evaluations of commercial chemicals in Canada, the United States, the European Union, and other countries aim to identify biodegradation rates of chemicals in natural soils and sediments. However, commonly used biodegradation testing methods are limited in their capacity to determine biodegradation rates under natural environmental conditions. As a result, widely varying biodegradation rates have been reported for many very hydrophobic substances. This variability causes difficulties in regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…However, in this case, concentration of these pollutants is not significantly reduced by the in-stream biotic and abiotic attenuation processes [81,84,89]. In a study by Riml et al [90], concentration of two PhACs, namely bezafibrate and metoprolol, was observed to be mainly reduced by sorption onto sediments, while the role of biotransformation and photolysis was insignificant.…”
Section: Surface Watermentioning
confidence: 73%
“…However, in this case, concentration of these pollutants is not significantly reduced by the in-stream biotic and abiotic attenuation processes [81,84,89]. In a study by Riml et al [90], concentration of two PhACs, namely bezafibrate and metoprolol, was observed to be mainly reduced by sorption onto sediments, while the role of biotransformation and photolysis was insignificant.…”
Section: Surface Watermentioning
confidence: 73%
“…In this way, those compounds become less exposed to other biotic (biotransformation) and abiotic (photolysis, volatilization) transformation processes and therefore become the least affected by the variation of environmental conditions between river segments. In this regard, a study using phthalate esters and their metabolites as test compounds showed that hydrophobic substances with high capacity to sorb to particulate organic matter were the least exposed to biodegradation, and were expected to have a low rate of biodegradation in natural sediments despite their inherent biodegradability (Kickham et al 2012). Similarly, another study on in-stream attenuation of pharmaceuticals identified sorption as the predominant attenuation mechanism for 3 compounds with relatively high K ow (bezafibrate, metropolol and naproxen) (Riml et al 2013), which were among the identified compounds with the lowest variability among river segments in our study.…”
Section: 3mentioning
confidence: 99%
“…Although the biotransformation reactions for MeFBSE and EtFOSE appear to be identical and are likely catalyzed by the same enzymes, and likewise between 6:2 FTOH and 8:2 FTOH, the decreased half-lives for the short-chain replacement chemistries may be more attributed to their increased bioavailability as a result of lowered sorption to sludge solids, as indicated by their lower log K OW values. The sorption of hydrophobic substances to solids can be a significant rate-limiting process which dictates biodegradation rates for substances catalyzed by the same enzymes [45].…”
Section: Environmental Implicationsmentioning
confidence: 78%